Neutron shielding characteristics of polymer composites with boron carbide - Tuna, Tuncay; Eker, Aysegul Akdogan; Kam, Erol (KOREAN PHYSICAL SOC, 2021)
In this study, the neutron shielding capabilities of boron carbide (B4C)-reinforced polyester-matrix composite materials were investigated. For the study, 20- 40- and 60-mm-thick specimens were first prepared by reinforcing with 10-50% B4C, and later their neutron shielding characteristics were studied by using various characterization techniques. The shielding capability of the composite materials was observed to increase with specimen thickness. In addition, increased amounts of B4C reinforcement improved the attenuation ratio of the material thereby increasing the shielding effectiveness. This trend, however, changed when the B4C ratio reached 40% and 50% at which a gradual decrease in neutron attenuation was observed. The experimental setup was also simulated using the Monte Carlo code MCNP-5, and similar computations were carried out. The experimental data almost completely agreed with computational results.
Keywords: Neutron radiation; Shielding; Polymer composite; B4C; Monte Carlo; Physics